Psychological Needs of the Female Main Character in Water for Elephants Movie using Maslow’s Hierarchy of Needs - Khoiriah, Umul Fajar; Haryanti, Dwi; Thoyibi, Muhammad; Haryanto, Sigit; Mansoor, Hafiza Sana (English Education: Jurnal Tadris Bahasa Inggris, 2024)
This study explores the psychological journey of Marlena, the female protagonist in the movie Water for Elephants, focusing on her fulfillment of psychological needs. The aim of this descriptive qualitative research is to analyze Marlena’s character development and the portrayal of her psychological needs within the narrative. The writer uses a contextual method in analyzing this movie. The writer analyzes the extrinsic aspects to show the fulfillment of Marlena’s psychological needs through the lens of Maslow’s Hierarchy of Needs. The result of this study is Marlena’s character in Water for Elephants demonstrates a gradual fulfillment of her psychological needs as depicted within Maslow’s Hierarchy of Needs framework, showcasing her development towards self-actualization amidst the challenges and dynamics of the circus environment. Through her experiences and interactions, Marlena embodies resilience and growth, illustrating the complexities of human motivation and fulfillment.